Financial Development and Its Effect on Inclusive Growth in Kenya 2000 - 2022 - Mutiiria, Onesmus; Nzomoi, Joseph; Kamoni, Peter (International Journal of Economics, 2024)
Purpose: In the past decade, Kenya's economy registered an average real GDP growth rate of 4.63 percent. Despite this growth, many people have been locked out of social and economic opportunities, with 19.1 percent of the Kenyan population living in poverty. This has intensified the need for inclusive growth, a growth model that promotes shared prosperity. Several studies have shown that financial systems that function well play a great role in the economy through the provision of key financial services that drive growth. However, there is a lack of substantial inquiry into financial development and inclusive growth in Kenya. This study sought to examine this relationship for the period 2000-2022. Methodology: The study employed a causal research design and used time series data that was collected from various databases. The level of inclusiveness in Kenya was analyzed using an inclusiveness matrix. An inclusive growth index was constructed, which was then used to empirically test the effect of financial development on inclusive growth. The data was presented in tables and figures. Findings: The inclusiveness matrix shows that despite positive economic growth rates, there is a low rate of equity growth, which shows that Kenya has a low level of inclusivity. The empirical results show that bank deposits and private-sector credit have a positive and statistically significant effect on inclusive growth. A 1% increase in bank deposits leads to a 0.074% increase in inclusive growth. When private-sector credit increases by 1%, inclusive growth expands by 0.070%. Bank return on assets has a positive but insignificant effect on inclusive growth. The study confirms that financial depth and access to financial services are the most conducive to inclusive growth in Kenya. Other determinants of inclusive growth include initial income, human capital development and macroeconomic stability. The overall findings suggest that financial development can be used to create economic opportunities for poor people in Kenya, thus reducing income disparities. Unique Contribution to Theory, Practice and Policy: The study has contributed to the ongoing conversation on inclusive growth, specifically on its measurement. The empirical results on the finance-inclusiveness nexus provide evidence-based policy interventions that can help in reducing income disparities and enhancing shared prosperity. The findings imply that policymakers and practitioners need to focus their attention on promoting financial access and financial depth in marginalized regions to create a significant impact on inclusive growth in Kenya.